Co-designing the Knowledge Management Model - Tamminen, P.; Weck. M.; Ferreira, F. (2020 Academic Design Management Conference, 2020)
This work-in-progress study reviews co-designing processes through the lens of possibility-driven design (PDD). A knowledge management model (KMM) is co-designed by facilitating the development work of senior and regional innovation actors who share ideas, experience and information in the development of smart products and services for an age-friendly smart living environment. The empirical part is divided into three stages: an orientation workshop, two panel meetings and three co-design and validation workshops where an appropriate knowledge management model is co-designed through iteration rounds. The first stage maps the regional innovation actors, relevant organisations in the region and data flows between all the parties. Ideas of suitable ways to manage knowledge are gathered from the panel meetings of the second stage and are methodologically supported by the strategic options development and analysis (SODA) approach. At the time of writing this paper, the third stage consisting of three workshops with appropriate iteration rounds is on-going. The findings of the study provide insights regarding the use of PDD activities with an inclusion of the SODA approach when facilitating the co-design of a KMM with a multi-professional group of experts. The study contributes to the theory of PDD by integrating systematic methodological aspects to it when working on complex problems.